Hydrogen-bonded frameworks crystals-assisted synthesis of flower-like carbon materials with penetrable meso/macropores from heavy fraction of bio-oil for Zn-ion hybrid supercapacitors - Fan, Huailin; Zhou, Shuxin; Li, Qingyin; Gao, Guoming; Wang, Yiran; He, Fei; Hu, Guangzhi; Hu, Xun (Journal of colloid and interface science, 2021)
The flower-like carbon from heavy fraction of bio-oil was synthesized with the assistance of hydrogen-bonded frameworks crystals and the penetrable meso/macropores across petal-like carbon was beneficial for electrolyte ion penetration and exchange. [Display omitted] The application of biomass-based carbon materials in electrode materials are usually subject to their deficient adsorption sites as well as sluggish diffusion of electrolyte ions. Herein, flower-like carbons are obtained from the heavy fraction of bio-oil with the auxiliary of Hydrogen-bonded frameworks (HOFs) crystals. During the co-carbonization of the both, the HOFs crystals are removed on account of its poor stability, which directs the formation of flower-like morphology and generates the penetrable meso/macropores across petal-like carbon nanosheets. In addition, the pyrolysis gases serve as the agents for activation to enrich the active sites without the further activation. The degree of graphitization and the contents of pyridine nitrogen for carbon materials could be flexibly adjusted with the contents of HOFs. Owing to the beneficial 3D flower-like structure, high specific surface area (1076 m2/g), large pore volume (2.59 cm3/g), and rational N species, the assembled Zn//BH-4 hybrid supercapacitor reaches a superior energy density of 117.5 Wh/kg at 890 W/kg and maintains 60.7 Wh/kg even at 16.2 kW/kg.